A systematic review and meta-analysis of treatment for hepatorenal syndrome with traditional Chinese medicine - Song, Tingxue; Guo, Xiaozhong; Shao, Lichun; Sun, Mingyu; Romeiro, Fernando Gomes; Han, Dan; Bao, Wenchun; Qi, Xingshun (Translational Gastroenterology and Hepatology; Vol 3 (August 2018): Translational Gastroenterology and Hepatology, 2018)
Background: Hepatorenal syndrome (HRS) is a life-threatening complication of end-stage liver diseases. It has been reported that traditional Chinese medicine (TCM) may improve liver function, delay disease progression, alleviate symptoms, and improve quality of life in HRS patients. The study aims to systematically review the efficacy of TCM for the treatment of HRS. Methods: Publications were searched electronically from China National Knowledge Infrastructure (CNKI), Wanfang, VIP, PubMed, and EMBASE databases. Odds ratio (OR) and standardized mean difference (SMD) with 95% confidence interval (CI) were calculated. Heterogeneity was assessed. The Cochrane Collaboration’s tool was used to assess the risk of bias. Results: Fourteen randomized controlled trials involving 788 patients with HRS were included. Random generation sequence was reported in only two studies. Blinding was not used in any study. Compared to conventional treatment without TCM, TCM led to a significant survival benefit during hospitalization (OR: 0.18; 95% CI: 0.08–0.39; P